Overlapping Land Conflicts: Effective Alternative Dispute Resolution Methods for License to Open State Land - Rahmatika, Nur Auliya; Herlindah , Herlindah; Hadiyantina, Shinta (Administrative and Environtmental Law Review, 2024)
This research focuses on an ideal model of mediation implementation that may be applicable as a strategy to increase the success of litigation on the License to Open State Land (LOSL). The research method is normative juridical research with a statutory and conceptual approach, using futuristic interpretation. As a regional government administrator, the Balikpapan Municipality Government has the authority to manage its own land sector. One of these authorities is realized through the implementation of the LOSL, which is organized through the Land and Spatial Planning Agency and the sub-district of Balikpapan Municipality. The implementation of the LOSL program within Balikpapan Municipality is inevitable due to the probability of disputes or disagreements. In accordance with this, the Balikpapan Municipality Regulation of LOSL and the Regulation of LOSL Implementation allow for the possibility of resolving LOSL disputes through mediation and/or litigation. Furthermore, although the settlement of LOSL disputes is expected to be resolved through mediation, its success rate has decreased since 2021. One constraining factor is the parties' low level of trust in the government. As a result, based on the above research, three ideal mediation models can be implemented to improve LOSL dispute resolution. These models are assumed to be a solution to the decreasing success rate of LOSL dispute resolution in Balikpapan Municipality. They are considered to increase society's trust in mediation as an inexpensive, fast, and simple alternative dispute resolution.